Evaluation of impurities in the Brazilian solar grade silicon and LeTID investigations in p-type multi-Si - Knob, Daniel (2019)
The cost reductions and the environmental benefits aligned with global concerns about climate change have made solar photovoltaic technology the most installed source of energy in the power sector worldwide. Brazil has the largest know reserves of silicon in the world. Therefore, there is a huge potential for developing a national technology for purifying and manufacturing silicon wafers within an increasingly competitive and efficient photovoltaic industry. The IPEN initiative of investigating the production of metallic silicon and metallurgical route purification required a characterization of samples in different stages of production from quartz to wafer and understanding the characterization methods for silicon wafers taking into account the main defect mechanisms such as light-induced degradation. Metalic silicon is produced in IPEN via magnesiothermal reduction through acid leaching to form a metallurgical grade silicon with relatively low impurities. One more acid leaching step resulted in a specific ultra-metallurgical grade silicon. The same acid leaching was processed in a commercially available Brazilian-made metallurgical grade silicon produced via carbothermal reduction. All samples impurities was measured by ICP-OES. The result is a material with ultra-metallurgical grade silicon content with excess of B and P. While wafer characterization was studied, an extensive investigation was taken on LeTID, which causes remain unknown, at Institute for Energy Technology, Norway. Neighboring high performance mc-Si p-type wafers were tested in different firing process conditions. The effects was investigated in terms of defects activation and a corresponding lifetime degradation and recovery at illuminated annealing. A sample with almost fully suppressed LeTID is shown. A new method have been proposed to separate Boron Oxygen-Light Induced Degradation effects of LeTID, enabling to measure even where it was thought to be fully suppressed. New models for LeTID defect formation and suppression are proposed. Both silicon purification and light-induced degradation characterization in mc-Si studies shows a wide range of research on new production routes that may require tailored processes of crystallization and solar cell manufacturing such as gettering and firing.